Organizational Culture Transformation Through the Leadership of the Principal at Sdn Sungai Taib in the Adiwiyata Program - Puspa Herliana; Dewi Aryani; Hendry Hermawan; Aslamiah Aslamiah; Celia Cinantya (Eduvest - Journal of Universal Studies, 2025)
This study aims to examine the contribution of the principal in implementing the adiwiyata program at SDN Sungai Taib, through an in-depth exploration of the principal's leadership role in creating an innovative and collaborative learning environment. The research method used is descriptive qualitative with data analysis using NVivo software. Data were collected through in-depth interviews, observations, and documentation. The research participants included the principal, the vice principal, and several teachers. The research results show that the principal's leadership significantly contributes to the successful implementation of the adiwiyata program by creating a learning environment that supports innovation and creativity. The principal also managed to overcome resistance to change and resource limitations through effective and communicative leadership strategies. In conclusion, the principal's contribution to implementing the adiwiyata program at SDN Sungai Taib is highly significant. Through visionary and inclusive leadership, the principal successfully transformed SDN Sungai Taib into a National Adiwiyata School.